Comparison between Two Different Two-Stage Transperineal Approaches to Treat Urethral Strictures or Bladder Neck Contracture Associated with Severe Urinary Incontinence that Occurred after Pelvic Surgery: Report of Our Experience. (24th April 2012) - Simonato, A.; Ennas, M.; Benelli, A.; Gregori, A.; Oneto, F.; Daglio, E.; Traverso, P.; Carmignani, G.
Abstract : Introduction. The recurrence of urethral/bladder neck stricture after multiple endoscopic procedures is a rare complication that can follow prostatic surgery and its treatment is still controversial. Material and Methods. We retrospectively analyzed our data on 17 patients, operated between September 2001 and January 2010, who presented severe urinary incontinence and urethral/bladder neck stricture after prostatic surgery and failure of at least four conservative endoscopic treatments. Six patients underwent a transperineal urethrovesical anastomosis and 11 patients a combined transperineal suprapubical (endoscopic) urethrovesical anastomosis. After six months the patients that presented complete incontinence and no urethral stricture underwent the implantation of an artificial urethral sphincter (AUS). Results. After six months 16 patients were completely incontinent and presented a patent, stable lumen, so that they underwent an AUS implantation. With a mean followup of 50.5 months, 14 patients are perfectly continent with no postvoid residual urine. Conclusions. Two-stage procedures are safe techniques to treat these challenging cases. In our opinion, these cases could be managed with a transperineal approach in patients who present a perfect operative field; on the contrary, in more difficult cases, it would be preferable to use the other technique, with a combined transperineal suprapubical access, to perform a pull-through procedure.